Facts and reflections on COVID-19 and anti-hypertensives drugs - Marín, Gustavo Horacio (2020)
Based on some publications that associate SARS-CoV-2 infection with the use of anti-hypertensive drug groups such as angiotensin-converting-enzyme inhibitors (e.g. enalapril) or angiotensin II receptor blockers (e.g. losartan), many patients from South America, Central America or Spain, have stopped or intend to interrupt their treatments with these drugs. Hence, it may exist ominous consequences due to this drop out. For this reason, it is necessary to quickly warn about this situation and the risks associated with it.